Protective effects of Brassica oleracea sprouts extract toward renal damage in high-salt-fed SHRSP. Issue 7 (July 2015) - Rubattu, Speranza; Di Castro, Sara; Cotugno, Maria; Bianchi, Franca; Mattioli, Roberto; Baima, Simona; Stanzione, Rosita; Madonna, Michele; Bozzao, Cristina; Marchitti, Simona; Gelosa, Paolo; Sironi, Luigi; et al.
<x xml:space="preserve">Abstract</x> Objectives: Renal damage precedes occurrence of stroke in high-sodium/low-potassium-fed stroke-prone spontaneously hypertensive rat (SHRSP). We previously reported a marked suppression of uncoupling protein-2 (UCP2) upon high-salt Japanese-style diet in SHRSP kidneys. Vegetable compounds are known to exert protective effects in cardiovascular diseases. We aimed at evaluating the impact of Brassica oleracea sprouts juice toward renal damage in Japanese diet-fed SHRSP and exploring the role of 5′-adenosine monophosphate-activated protein kinase (AMPK)/NAD-dependent deacetylase sirtuin-1 (SIRT1)/peroxisome proliferator-activated receptor-γ coactivator-1α (PGC1α)/peroxisome proliferator-activated receptor-α (PPARα)/UCP2 axis. Methods: SHRSP received Japanese diet for 4 weeks. A group of SHRSP received Japanese diet and B. oleracea. A third group received Japanese diet, B. oleracea, and PPARα inhibitor (GW6471). A group of SHRSP fed with regular diet served as control. Results: Japanese diet induced marked increases of oxidative stress, inflammation, and proteinuria, along with glomerular and tubular damage, as compared with regular diet. A significant suppression of AMPK/UCP2 pathway was observed. Despite Japanese diet feeding, concomitant administration of B. oleracea prevented oxidative stress accumulation, inflammation, renal damage, and proteinuria. All components of the UCP2 regulatory pathway were significantly increased by B. oleracea. Superoxide dismutase 2 and phosphoendothelial nitric oxide synthase were also stimulated. Addition of PPARα inhibitor to B. oleracea and Japanese diet significantly reduced the B. oleracea beneficial effects. SBP levels were comparable among the different groups of rats. In vitro, UCP2 inhibition by genipin offset the antioxidant effect of B. oleracea in renal mesangial and proximal tubular cells. Conclusion: B. oleracea administration prevented renal damage in salt-loaded SHRSP, independently from SBP, with parallel stimulation of AMPK/SIRT1/PGC1α/PPARα/UCP2 axis. Stimulation of the latter mechanism may provide relevant renal protective effect and play a therapeutic role in target organ damage progression in hypertension.